2018
DOI: 10.1063/1.5049144
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Strong microwave photon-magnon coupling in multiresonant dielectric antennas

Abstract: Achieving quantum-level control over electromagnetic waves, magnetisation dynamics, vibrations and heat is invaluable for many practical application and possible by exploiting the strong radiation-matter coupling. Most of the modern strong microwave photon-magnon coupling developments rely on the integration of metal-based microwave resonators with a magnetic material. However, it has recently been realised that all-dielectric resonators made of or containing magneto-insulating materials can operate as a stand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 139 publications
0
15
0
Order By: Relevance
“…Our results should find practical applications in the emergent research directions of liquid optomechanics [36][37][38][39][40][41] and hybrid metamaterial structures [42][43][44]. Thus far, optomechanical structures have mostly been implemented by using the solid-state technology [45] because modern electronic, photonic and phononic devices and circuits are based on solid-state platforms.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our results should find practical applications in the emergent research directions of liquid optomechanics [36][37][38][39][40][41] and hybrid metamaterial structures [42][43][44]. Thus far, optomechanical structures have mostly been implemented by using the solid-state technology [45] because modern electronic, photonic and phononic devices and circuits are based on solid-state platforms.…”
Section: Discussionmentioning
confidence: 94%
“…Although large and increasing theoretical effort has been made to recreate and utilise these nonlinear phenomena in solid-state configurations [42,43,[49][50][51][52][53], considerable stiffness of solid-state structures requires impracticably high powers to access the nonlinearity. This is in stark contrast with fluids whose softness [54] allows accessing their nonlinear properties with low power signals produced and controlled by modern photonics devices such as optical fibres and integrated-circuit resonators [36][37][38][39][40][41]44].…”
Section: Discussionmentioning
confidence: 99%
“…However, in that system the spacing between the peaks of the comb was only 20–40 Hz. Whereas frequency combs with a Hz-range spacing can find certain applications 17 , in the gas bubble system investigated in the present work we use the high-kHz range that can potentially be extended to the high-MHz range 24 . This opens up opportunities for using acoustic combs instead of optical ones or in addition to them in a number of practical situations where operation at higher frequencies may be required 16 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, considerable attention has recently been paid to exploiting novel regimes of strong coupling between different entities such as photons, phonons and magnons [121,122]. It has been suggested that multi-resonant photonphonon-magnon interaction can be achieved with magnetofluidic droplets which combine the softness of fluids with the ability of solids to support resonances of electromagnetic, acoustic and spin waves [123].…”
Section: Fig 6: Comparison Between (A) a Theoretical Capillary Oscilmentioning
confidence: 99%